Field notes contributed by Erik Munson, spring 1987 - Munson, Eriket al (1987)
List of birds and locations contributed by Erik Munson. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of spring 1987. Epson - sheet feed